Khởi đầu tốt, nhưng chưa phải đã hoàn thành : (The World Bank, 2012)
This report examines the lives of poor men, women, and children and explores the constraints and opportunities they face today in rising out of poverty. It builds on a rich body of poverty analysis and an excellent base of knowledge from previous reports and aims to do three things. First, it proposes revisions to Vietnam's poverty monitoring system - via better data, updated welfare aggregates, and new poverty lines - to bring these more in line with economic and social conditions in present-day Vietnam. Second, it revisits the stylized facts about deprivation and poverty in Vietnam, and develops an updated profile of poverty using data from the 2010 Vietnam Household Living Standards Survey (VHLSS) and new qualitative field studies. Third, it analyzes some of the key challenges for poverty reduction in the next decade, including changing regional patterns of poverty and wealth, high and persistent poverty among ethnic minorities, and rising inequality in outcomes and opportunities.